Singapore : Workforce Development - World Bank (Washington, DC, 2014)
Singapore provides an example of a small nation in which Workforce Development (WfD) has been a primary component of economic development from the outset. WfD has received consistent support and advocacy as a result. WfD in this context refers to preparation of the future workforce via basic through to tertiary level education, and up-skilling of the existing workforce via continuing and professional education and training, covering a broad span of activities. As will be seen in the report, the early years of nationhood saw a much greater emphasis on basic, universal education and technical skills, to support the policy of growing jobs and reducing high unemployment. Whereas, from the 1980s, changing economic circumstances meant that upgrading the skills of the existing workforce took on increased importance. The tool is based on an analytical framework that identifies three functional dimensions of WfD policies and institutions: strategic framework, which refers to the praxis of advocacy, partnership, and coordination in relation to the objective of aligning WfD in critical areas to priorities for national development; system oversight, which refers to the arrangements governing funding, quality assurance and learning pathways that shape the incentives and information signals affecting the choices of individuals, employers, training providers and other stakeholders; and service delivery, which refers to the diversity, organization and management of training provision, both state and non-state, that deliver results on the ground by enabling individuals to acquire market-and job-relevant skills. These three dimensions constitute a closed policy-making loop and, when taken together, allow for analysis of the functioning of a WfD system as a whole. This report focuses specifically on policies in the area of WfD.